Basic endurance performance is highly correlated to mean heart rate in female top level handball players - Platen, P.; Manchado, C. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Players of the German female national team wore heart-rate- (HR-) monitoring belts during 7 matches of the EC in 2004. The players had a mean action time of 41.4 ± 15.2 min, mean HR was 161.7 ± 11.9 bpm, corresponding to 85.8 ± 3.2 % of HRmax. Velocity corresponding to 4 mmol/l lactate (v4) was negatively correlated with mean %HRmax. This is a clear indicator for the necessity of the development of a high aerobic capacity in international female top level handball.